2022
DOI: 10.1097/hcr.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comprehensive Cardiac Rehabilitation in Elderly Patients With Acute Heart Failure

Abstract: Figure. Comparison of (A) 6-mo mortality and (B) home discharge rate before propensity score matching; (C) 6-mo mortality and (D) home discharge rate after propensity score matching. Abbreviation: CCR, comprehensive cardiac rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…What is more, multidisciplinary cardiac rehabilitation seems to be better than exercise-based cardiac rehabilitation. Recently, a retrospective cohort study 39 indicated that compared with a single rehabilitation physiotherapy group, patients in the multidisciplinary cardiac rehabilitation group showed higher left ventricular ejection fraction. Therefore, considering the limited number of studies and participants in our meta-analysis, it remains unconfirmed whether exercise rehabilitation can improve cardiac function in patients with AHF and should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, multidisciplinary cardiac rehabilitation seems to be better than exercise-based cardiac rehabilitation. Recently, a retrospective cohort study 39 indicated that compared with a single rehabilitation physiotherapy group, patients in the multidisciplinary cardiac rehabilitation group showed higher left ventricular ejection fraction. Therefore, considering the limited number of studies and participants in our meta-analysis, it remains unconfirmed whether exercise rehabilitation can improve cardiac function in patients with AHF and should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%